Totua Ngata dan Konflik (Studi atas Posisi Totua Ngata sebagai Lembaga Adat di Kecamatan Marawola) - Hendra Hendra (Antropologi Indonesia, 2013)
Talking about tradition, it is kind of imagination of kinship in the past in an idealism positions in an orderly and harmonious level. Everyone respect each other and take position in the clan and their class respectively. The aims of this paper is to find out information about the institutions traditional role in the District Marawola to the conflict in the community. The research start with a literature study then continued with observation and interviews. This paper apply govern mentality theory that triggered by Michael Foucault. The results that found in this research that the traditional institutions began to lose its role, some of which are caused by the gap between the old and the young in the communities itself. Traditional institutions also lose their social legitimacy that seen from the shrinking role of traditional institutions, where traditional institutions only deal with traditional healing rituals, clearing land and harvesting rituals. Rules of traditional institutions such as law regulatory with sanctions are applied only in the form of oral speech in memory of the past in the absence of compliance with customary rules itself.Key-words: Customs, Totua Ngata, Governmentality, Conflict